1980
DOI: 10.1139/m80-217
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of response to copper, cadmium, and lead by a blue-green and a green alga

Abstract: The toxic metal ions Cu2+, Cd2+, and Pb2+ inhibited growth of the green alga Ankistrodesmus braunii and the blue-green alga (Cyanobacterium) Anabaena, strain 7120. Some concentrations of Cu lysed Anabaena 7120 at early, but not late, stages of growth. The other metals inhibited growth without causing lysis. Adding the chelating agent nitrilotriacetic acid (NTA) did not reduce, and in some cases increased, metal toxicity to Anabaena 7120. This suggests that these metals do not act on this alga only in the ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…The ability of cyanobacteria to accumulate heavy metals and radionuclides from their external environment has been demonstrated in several studies (Horikoshi et al 1979, Stratton & Corke 1979a, b, c, Baxter & Jensen 1980, Laube et al 1980, Massalski et al 1981, Jensen et al 1982, Wang & Wood 1984, Pettersson et al 1985a, Fischer 1985, Verma & Singh 1990, Avery et al 1991.…”
Section: Introductionmentioning
confidence: 98%
“…The ability of cyanobacteria to accumulate heavy metals and radionuclides from their external environment has been demonstrated in several studies (Horikoshi et al 1979, Stratton & Corke 1979a, b, c, Baxter & Jensen 1980, Laube et al 1980, Massalski et al 1981, Jensen et al 1982, Wang & Wood 1984, Pettersson et al 1985a, Fischer 1985, Verma & Singh 1990, Avery et al 1991.…”
Section: Introductionmentioning
confidence: 98%
“…The effects of Cu have been widely studied in red blood cells (1,20), rat hepatocytes (28), frog skin (10), and marine flagellates (15,25,26). In several of these studies Cu has been suggested to affect the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Thus methylated mercury compounds are more toxic than the Hg2+ ion (NUZZI, 1972) and vitamin B12 is one of the most available forms of cobalt known, Furthermore there is evidence that ligands such as citrate and nitrillotriacetate increase the toxicity of copper to green and blue-green algae (cyanobacteria) (GUY and KEAN, 1980;LAUBE et al, 1980). LAEGREID et al (1983) found a higher cadmium toxicity to Selenastrum capricornutum Printz than expected from the Cd 2+ concentration.…”
Section: Solubilitymentioning
confidence: 99%